The Knowledge Based Agricultural Bioeconomy: A Bibliometric Network Analysis - Christina-Ioanna Papadopoulou; Efstratios Loizou; Katerina Melfou; Fotios Chatzitheodoridis (Energies, 2021)
The last ten years have witnessed an increase in publications focusing on bioeconomy as a proposal to confront the global challenges of climate change, depletion of non-renewable resources and ecosystem degradation. This paper investigates the scientific literature on issues related agricultural bioeconomy by applying a bibliometric network analysis. Bibliometric analysis is applied to the publications of the Scopus database during the period 2010–2020 in order to provide an overview of the main aspects that characterize agricultural bioeconomy. The results showed that out of a total of 1100 scientific papers, only 2.45% were published in 2010, while the corresponding share in 2020 was 20.81%. In the five years of 2016–2020, cumulatively, 70.63% of the publications were made, showing the dynamic evolution of bioeconomy. In addition, out of 85 countries in total, Germany and Italy are the two countries with most publications, while the fragmentation of research is evident with the creation of two main nodes, the European and the American. Moreover, keyword analysis showed that biomass and sustainability are two main recurring concepts, confirming that, currently, bioeconomy operates at three different levels: energy demand, land demand, and governance. It is apparent that to boost the development of agricultural bioeconomy, the following aspects should be assessed: the effective use of resources, an understanding of the key drivers of agricultural bioeconomy, and a clear perception of their associations. There is still no consensus as to which are the key factors that will accelerate its sustainable development. Our pursuit is to use the tools of bibliometric analysis to reach more critical conclusions regarding the agricultural bioeconomy, rather than approach it in a static way.